The Role of Subsidiary Manager under Resource-Based Paradigm - Harris Turino Kurniawan (Sekolah Tinggi Manajemen IPMI, 2018)
The role ofsubsidiary managers, as middle managers in Multinational Corporation (MNC) structure, has received increasing scholars' attentions recent time. They are believed to have great inluences to facilitate various strategic activities, especially in developing subsidiary capability, hence contributing to subsidiary development.Research to investigate subsidiary manager roles and managerial process in subsidiary level, however, are relatively rare. I propose an alternative framework to ill the gap, by employing recent development of resource-based theory, i.e. resource orchestration. I argue that subsidiary manager can be treated as a mediator between resource allocated by corporate headquarter (and also from local partners in strategic alliance formation) and the various steps in resource orchestration